A single microwire near-infrared exciton–polariton light-emitting diode. Issue 3 (12th January 2021) - Jiang, Mingming; Tang, Kai; Wan, Peng; Xu, Tong; Xu, Haiying; Kan, Caixia
Abstract : Exciton-polariton LED composed of a ZnO:Ga MW and p-GaAs template serving hole supplier is demonstrated, and its working characteristics in the near-infrared spectrum. Abstract : Exciton–polaritons, which originate from the strong coupling between photon modes of microresonators and excitons in semiconductor micro-/nanostructures, have drawn much attention due to their significance for fabricating coherent light sources which possess considerably lower emission thresholds. In this study, an exciton–polariton light-emitting diode (LED), made from a Ga-doped ZnO microwire (ZnO:Ga MW) and a p-GaAs template serving as the hole supplier, is fabricated. The n-ZnO:Ga MW/p-GaAs heterojunction device can emit light with a near-infrared wavelength of 880 nm and a narrow line width of about 60 nm. Due to the high quality whispering gallery mode (WGM) microcavities which are naturally self-constructed by the hexagon-shaped MW, the electroluminescence (EL) spectrum resolves into a series of resonance peaks which can be assigned to exciton–polariton features, leading to the strong coupling of the exciton and the WGM photon in the as-fabricated LED. The strong exciton–photon coupling is clearly evidenced via angle-resolved EL measurements, with the Rabi splitting energy extracted as 160 meV. Furthermore, by adjusting the size of the WGM microcavity structure naturally formed by the hexagonal MWs, particularly by adjusting the diameter of the wires, the exciton–polariton coupling strength in the single MW based LEDs can be tuned, with the as-extracted Rabi splitting energy varying in the range of 92–294 meV. The realization of a single MW based LED, which shows exciton–polariton behavior from a built-in optical microresonator, can enable a promising route for the future fabrication of polariton emitters, where the device performance no longer suffers from obstacles including the need for additional optical resonators, large lattice mismatch, and template availability.